LEGAL CERTAINTY OF LAND SALE AND PURCHASE DEED THAT HAS NOT BEEN SIGNED BY PPAT AND LEGAL PROTECTION FOR BUYERS - Dewi Wulandari; Isdiyana Kusuma Ayu (Fakultas Keguruan Dan Ilmu Pendidikan Universaitas PGRI Banyuwangi, 2026)
This study analyzes the legal certainty of the Sale and Purchase Deed (AJB) that has not been signed by the Land Deed Making Officer (PPAT), the legal implications for buyers, and the forms of legal protection available. Using juridical-normative research methods with legislative, conceptual, and case approaches, this study found that AJB without PPAT's signature was degraded into a deed under hand, so it could not be used as a basis for registration of transfer of rights. The legal implication is that the transformation of rights from obligatoir to zakelijk is delayed, leaving buyers vulnerable to collateral confiscation, inheritance, and double selling. Legal protection is realized preventively through the blocking of land books and the creation of PPJB by Notaries, as well as repressively through lawsuits for Unlawful Acts and complaints to the PPAT Board of Trustees and Supervisors.